Dissecting functions of SEPALLATA‐like MADS box genes in patterning of the pseudanthial inflorescence of Gerbera hybrida. Issue 3 (25th July 2017) - Zhang, Teng; Zhao, Yafei; Juntheikki, Inka; Mouhu, Katriina; Broholm, Suvi K.; Rijpkema, Anneke S.; Kins, Lisa; Lan, Tianying; Albert, Victor A.; Teeri, Teemu H.; Elomaa, Paula
Summary: The pseudanthial inflorescences of the sunflower family, Asteraceae, mimic a solitary flower but are composed of multiple flowers. Our studies in Gerbera hybrida indicate functional diversification for SEPALLATA ( SEP )‐like MADS box genes that often function redundantly in other core eudicots. We conducted phylogenetic and expression analysis for eight SEP ‐like GERBERA REGULATOR OF CAPITULUM DEVELOPMENT ( GRCD ) genes, including previously unstudied gene family members. Transgenic gerbera plants were used to infer gene functions. Adding to the previously identified stamen and carpel functions for GRCD1 and GRCD2, two partially redundant genes, GRCD4 and GRCD5, were found to be indispensable for petal development. Stepwise conversion of floral organs into leaves in the most severe RNA interference lines suggest redundant and additive GRCD activities in organ identity regulation. We show conserved and redundant functions for several GRCD genes in regulation of flower meristem maintenance, while functional diversification for three SEP1/2/4 clade genes in regulation of inflorescence meristem patterning was observed. GRCD genes show both specialized and pleiotropic functions contributing to organ differentiation and flower meristem fate, and uniquely, to patterning of the inflorescence meristem. Altogether, we provide an example of how plant reproductive evolution has used conserved genetic modules for regulating the elaborate inflorescence architecture in Asteraceae.